Blood on the streets - Bethnal Green and Stepney Trades Council report, 1978 (London, 1978)
1978 1974-79 "Blood on the streets - Bethnal Green and Stepney Trades Council report, 1978" [BW0015], 1978, Trades Union Congress This report by the Bethnal Green and Stepney Trades Council details racial attacks in the East End of London during the period 1976-1978, the role of the National Front, and the response of local police. Artist Dan Jones.